The Metaphysics of Time Within Physics - Ahmed, Mohamed (AUC Knowledge Fountain, 2025)
The starting point of this thesis is to shed some light on the metaphysical nature of time by reflecting on the physics of time. The aim of this approach is not to [dis]prove or defend a metaphysical position but rather to elucidate the metaphysical position that underlies [or is compatible with] our best scientific theories. This task will be demanding, not only because our best theories may carry different interpretations of their underlying temporal structure but also because there seems to be a conceptual conflict/incompatibility between the notion of time in relativity and quantum mechanics, which are the two major physical theories. We explore how Quantum Mechanics (particularly the violation of Bell’s Inequality) challenges the eternalist picture of time, the principle of relativity of simultaneity, and the notion of local causality in relativity. Three reconciliation strategies between the two theories are reviewed and assessed, along with their respective views of time.